Dampak Pembelajaran Aqidah Akhlak terhadap Sikap dan Sopan Santun Peserta Didik di Sekolah IT Dinamika Umat - Indah Berliana Suwandi; Gunawan Ikhtiono; Sutisna Sutisna (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2022)
Moral education is very important for every human being among educational institution, the behavior attitudes and courtesy of student are prioritized because they reflect student who have good character. Therefore, learning aqidah morals has the ain of forming patterens of behavior, attitudes and manners of student through learning on the subjects of aqidah morals, so that the implementations of learning aqidah morallity can be realized optimally. The purpose of this research is to determine the impact of learning aqidah morals and to know the teacher’s ability to cultivate the polite attitude of students. The method in thos study uses a case study approach, wich is a method for collecting and analyzing data on particular case.The result of this research are that students geta good important and learn moral aqidah so that they can practice it in everyday life an always get used to being polite to those who are older, such as getting used to the 5 S(greeting, greeting, polite, smile and sharing) they always do. Do it every time you meet the teacher or someone who is older. The ability of the teacher to cultivate the polite attitude of students is by giving example of good things. There are the behavior of students, namely internal factors, two namely factors that influence that originate from and with themselves. Student such as the character or character of each student. While the second factor is external factors, namely factors that come from the environment of students. Therefore, the role of parents and teachers is needed for the development of students. Keywords : Moral Akhlak, Polite Attitude